WHISTLEBLOWING FOR FRAUD: PERSPECTIVE OF LEADERSHIP TYPES AND ACCOUNTABILITY PRESSURE - Aulia Damar Sustika; Intiyas Utami; Aprina Nugrahesthy Sulistya Hapsari (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The increasing number of frauds has become a serious threat to stakeholders. The best method for preventing fraud is to disclose fraud in an organization. This study aims to examine the potential for whistleblowing actions undertaken by employees under transformational and transactional leadership styles. The method used in this study is a 2x2 experiment between research subjects involving 96 undergraduate students of a state university in Central Java. The results of this study prove that the subjects have greater whistleblowing intentions when they are under transformational leadership than transactional leadership, the subjects have greater whistleblowing intentions when they are under high accountability pressure than low accountability pressure, and the interaction between transformational leadership and high accountability pressure has a significant influence on whistleblowing intentions.